1993
DOI: 10.1063/1.464438
|View full text |Cite
|
Sign up to set email alerts
|

Clustered water adsorption on the NaCl(100) surface

Abstract: The adsorption dynamics of water on NaCl(100) is studied by molecular dynamics calculations as a function of coverage. We find that, starting from a critical coverage of about 1/2 monolayer, a coupling of the water dipoles sets in and the interaction between the water molecules wins over the interaction between adsorbate and substrate leading via percolation to formation of infinite cluster networks. This effect is confirmed qualitatively by surface sensitive optical second harmonic measurements with well-cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
76
0

Year Published

1995
1995
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(88 citation statements)
references
References 32 publications
12
76
0
Order By: Relevance
“…11 We never observed the water-induced NaCl ͑4 ϫ 2͒ reconstruction, that appears under electron irradiation as reported in literature. 12,13 We therefore conclude that all water was removed successfully by the propanol rinse.…”
mentioning
confidence: 89%
“…11 We never observed the water-induced NaCl ͑4 ϫ 2͒ reconstruction, that appears under electron irradiation as reported in literature. 12,13 We therefore conclude that all water was removed successfully by the propanol rinse.…”
mentioning
confidence: 89%
“…This evidence comes from scanning polarization force microscopy (SPFM) measurements at finite humidity which have shown that water condenses into solidlike polygonal domains in angular epitaxial relationship with the underlying mica surface [6,7]. The stability of this phase at room temperature is rather unusual since previously reported icelike structures on metals [1] and on insulators [8,9] have been observed in ultrahigh vacuum (UHV) only at low temperatures.…”
mentioning
confidence: 92%
“…In the last five years several different techniques have been applied to study the adsorption of water on both monocrystalline NaCl surfaces and epitaxially grown NaCl films on a Ge͑100͒ substrate in UHV conditions. [11][12][13][14] A FTIR spectroscopy study of D 2 O adsorption on a single crystal NaCl surface provided no evidence for a 2D phase transition and the formation of an ordered adsorbed layer. 13 Two types of spectra were found, ascribed to an incomplete 2D disordered layer and to 3D ice.…”
Section: Introductionmentioning
confidence: 99%